Novel Thick-Film Piezoceramic Micro-Generator Based on Free-Standing Structures - White, Neil; Harris, Nick; Kok, Swee Leong; Tudor, John (2008)
Thick-film piezoelectric free-standing structures fabricated with a combination of conventional thick-film technology and a sacrificial layer technique are presented. The structures were fabricated in the form of composite cantilevers, consisting of lead zirconate titanate (PZT) as the functional element and silver/palladium (Ag/Pd) as the electrodes. The cantilevers are free standing above a substrate and are able to operate at low levels of vibration suitable for harvesting energy from the environment. An open circuit output voltage of 130 mV was measured from a sample of length 18 mm, width 9 mm and PZT thickness of 80 μm. The sample was found to produce a maximum output electrical power of 10 nW at its resonant frequency of 237.5 Hz and acceleration level of 0.981 m/s2 when driving a 60 kΩ resistive load. The output power was found to increase exponentially with acceleration. At an acceleration of 9.81 ms-2, 270 nW of power was produced. The output power can be improved by attaching a proof mass at the tip of the cantilever beam. A beam having a proof mass of 1.14 g, resulted in an eight-fold improvement of output power compared to a device with no added proof mass at the same acceleration level of 0.98 ms-2.